The Good Governance for Using the Authority of Local Administration Officer - Laoboonsangiem, Santi (Journal for Developing the Social and Community, 2021)
Abstract This research aim to study (1) Concepts, theories and principles related to local government, (2) Analyze good governance in international dimensions and Thailand, (3) Analyze the good governance principles for the exercise of duties of the Local Administration Officer (Village headman) and (4) Establish good governance principles for using the authority of Local Administration Officer. The research data source consists of (1) Documentary research were Concepts, theories and principles from textbooks, research reports, and articles, both Thai and foreign, specifically those related to good governance and the law on international governance in foreign countries and Thailand. (2) In-depth interview was the person directly related to the governing body which is the direct supervisor is (1) Vice Governor (2) Deputy Governor (3) District Chief Officer and (4) Assistant District Chief Officer. Using the content analysis. The research results found that; 1. The Local Governing Act B.E. 2414 states that in a district area consisting of sub-districts and villages, in this regard, considering the smallest administrative unit, which is considered a strategic area that is crucial to the direction and development of the country or It can be said that the breaking point or the foundations of development are the sub-districts and villages which have local rulers who are government officials to govern the people in the sub-districts called Kamnan and in the village area called the village headman. 2. The principles of good governance of international organizations include the rule of law, transparency, responsibility, participation, effectiveness, efficiency and consensus. However, principles of good governance in the dimension of Thailand in accordance with the Royal Decree on Principles and Procedures for Good Government Administration 2003, namely the rule of law, virtue, transparency principle, principles of participation, principle of responsibility, value principle. 3. The principles of good governance for the exercise of duties of the local guardians consist of 8 principles which are 1) the rule of law 2) meet the needs of the people 3) Transparency 4) Morality 5) Participation 6) Consensus 7) Efficiency and effectiveness and 8) Responsibility 4. The model of good governance for using the authority of Local Administration Officer must leads to the establishment of Participatory design, Co-design) for the stakeholder jointly design a suitably.